Association between Advanced Paternal Age and Low Birthweight in Thai Population - Pawan Limvorapitux; Buraya Phattanachindakun; Pornpimol Ruangvutilert (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
Objectives: To determine the association between advanced paternal age and low birthweightMaterials and Methods: This was a case-control study including primigravida women, age ≥ 18 years old, who delivered at Siriraj Hospital during January 2008 to December 2010. This study included 398 women who delivered the low birthweight infants. Matching total of 400 women with infant weight ≥ 2,500 g were served as the control group. Paternal age, parental characteristics and certain obstetric complications were compared between these two groups.Results: There was no statistically significant associations between paternal age older than 34 years old and low birthweight. Maternal age younger than 20 years had an increased risk of having a low birthweight infant comparing with the mothers aged 20-34 years (adjusted OR 2.31, 95%CI: 1.14-4.71). Severe preeclampsia, superimposed preeclampsia and eclampsia are significantly increased the risk of low birthweight (adjusted OR 3.59, 95%CI: 1.65-7.82). The association between preterm birth and low birthweight was remarkably significant (adjusted OR 16.06, 95%CI: 10.07-25.63).Conclusion: Advanced paternal age is not associated with low birthweight in Thai population. Teenage pregnancy, pregnancy associated hypertension at the level of severe preeclampsia or more, and preterm birth increased risk of low birthweight.